The impact of metacognitive learning techniques on learners’ essay writing performance: a study on pre-service teacher students at Teacher Training School of Bouzeareh - Lebci, Zahra; Abdulhameed, Kamoludeen Olasunkanmi; Zubairi, Ainol Madziah (Asian Scholars Network, 2022)
This study was carried out to investigate whether pre-service teacher students are aware of using Metacognitive Learning Techniques (MLT) in writing their academic essays, and to explore which metacognitive learning Techniques (MLT) is mostly adopted by the students in essay writing. The study also examined the significant relationship between MLT and students’ essay writing performance (EWP) and established which MLT is a predictor of students’ EWP depending on the views of pre-service teacher Training School of Bouzareah students, Algeria. The questionnaire employed was adapted from Farahanian’s MLWQ. The data was analysed using SPSS V28 by employing the mean scores, correlation matrix, and regression. The findings indicated that most of the respondents are aware of using metacognitive learning strategies in their essay writing and that Planning, Organization, and Goal setting were the commonly used strategies by the students. The results identified a substantial connection between MLT and students’ performance in essay writing. And that Awareness was found to be the only predictor of students’ EWP. The study, therefore concluded that students do not only learn effectively by using metacognitive writing strategies but also can transfer skills learned beyond the classroom activities. This implies that metacognitive strategies-based teaching is highly essential and beneficial as the influence of metacognitive learning strategies (awareness) has been established in this study as part of the reasons behind students’ essay writing performance. By implication, higher institutions of learning, as well as education policymakers, are urged to include metacognitive learning techniques into the pedagogical approaches and make necessary emphasis on its usage.